Insulin Therapy with Personal Insulin Pumps and Early Angiopathy in Children with Type 1 Diabetes Mellitus - Joanna Tołwińska; Barbara Głowińska-Olszewska; Artur Bossowski (Hindawi Limited, 2013)
Objective. Assessment of the effect of a treatment method change from multiple daily insulin injection (MDI) to continuous subcutaneous insulin infusion (CSII) on the development of early angiopathy in children with T1DM with or without retinopathy. Methods. The study pump group involved 32 diabetic children aged 14.8, with the initial HbA1c level of 8.3%, previously treated by MDI. The patients were examined before pump insertion and after 3 and 6 months of CSII. We assessed HbA1c level, carotid artery intima-media thickness (c-IMT), and flow-mediated dilatation (FMD) of the brachial artery. The pump group was compared to a group of eight teenagers with diagnosed nonproliferative retinopathy, treated with MDI. Results. HbA1c in the entire group was found to improve in the second and in the third examination. During 6 months of CSII, FMD increased and IMT decreased. Retinopathic adolescents had significantly thicker IMT and lower FMD compared to baseline results of the pump group. Treatment intensification in the retinopathy-free children enhanced these differences. Conclusions. CSII is associated with lower IMT and higher FMD. Whether on the long-run CSII is superior to MDI to delay the occurrence of diabetes late complications remains to be explained.